A variação linguística no ensino de língua portuguesa: uma reflexão sobre o contexto de sala de aula no colégio Palmira Gabriel de Barcarena-PA - SANTOS, Franciele Lima Beltrão (2019)
The present work, it is a practice reflective through an account of experience, concerning teaching of variation linguistics in the classroom with students of the 1st year high school, college state Palmira Gabriel of Barcarena-Pará. The proposal brings how to approach the sociolinguistics, which enables us to the study of variations language under school. Language in the design of sociolinguistas is intrinsically heterogeneous, in this sense, the language is not used in order homogeneous for all your speakers. The use of a language varies according to the time, region, social class and so on. Depending on the situation, the same individual can make use of different varieties language adapting to each context of communication. When working linguistic diversity, we intend to show that the Portuguese not presents itself uniform throughout the Brazilian territory. Based in thisstudy, we can theoretical assumptions main, Tarallo (1994), the PCNs (1998), Bagno (2002, 2007a, 2007b) and Bortoni-Ricardo (2004) that provide valuable contribution to the teaching of varieties language. Research-actions tarted with observations, implementation of a questionnaire 10 questions objective with order to probe the knowledge of students in relation to the subject, and then intervimos through a workshop with lectures and practices. The practice teaching occurred in two times, November 2017 and December 2018. Search results give the analysis of questionnaires and experience report.